Uganda : Report on the Prices Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report discusses technical advice and recommendations given by the IMF mission to the authorities of Uganda about finalizing the rebased producer price index (PPI) and developing export and import price indices (XMPI). It is proposed that the new PPI and the XMPI be compiled using a modified and enhanced version of the current PPI Excel-based processing system. Considerable time was spent with the XMPI team explaining the required functionality, and a partial compilation of the import price index was undertaken using Excel spreadsheets. For the PPI, an index structure and weighting pattern have also been derived based on the final 2009-10 supply and use tables.